Reform of the fiscal framework of the European Union and impact review - Andraž Konc (Političke Perspektive, 2025)
This article explores the reform of the European Union’s fiscal framework, focusing on the evolution of fiscal rules, their implications, and the recent updates introduced in 2024. The analysis begins with an overview of the EU’s fiscal governance structure, emphasizing its historical foundations in the Maastricht Treaty and subsequent reforms. The study employs a review-based methodology, analysing key policies such as the Stability and Growth Pact, the Fiscal Compact, and the European Semester. The 2024 reform is critically examined, highlighting its central aim to ensure sustainable public finances while enabling counter-cyclical policies and addressing macroeconomic imbalances. The findings indicate improved flexibility and sustainability compared to prior frameworks, yet challenges persist, such as balancing fiscal discipline with necessary investments in transnational public goods and addressing disparities among Member States. We contribute to understanding the complexities of EU fiscal governance and offer insights into future policy directions to enhance economic resilience and integration.